Analysis of Students Spatial Thinking Ability Improvement Through Story Maps Learning Using the Wilcoxon Signed Rank Test - Putri, Davina Aulia; Putri, Hafiziani Eka (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2026)
Spatial thinking is an important skill in geography learning, but student learning outcomes often show variations influenced by learning methods and media. This study aims to analyze the improvement of students’ spatial thinking skills through the use of StoryMaps media using the non-parametric Wilcoxon Signed Rank Test. The study was conducted with a descriptive quantitative approach through pretest and posttest measurements on 30 students. Data were analyzed using the Shapiro–Wilk test to test for normality and the Wilcoxon test to see differences in abilities before and after learning. The results of the analysis showed a Z value of -4.793 with a significance of 0.000. Since the significance value of 0.000 <0.05, it was concluded that there was a significant increase in students’ spatial thinking skills after participating in StoryMaps-based learning. These findings indicate that interactive geospatial media can make a real contribution to improving students’ spatial understanding. Thus, the use of StoryMaps can be an effective alternative learning media, while further evaluation needs to consider additional variables to optimize learning outcomes.